Accuracy of nutritional assessment tools for predicting adverse hospital outcomes Fiabilidad de los instrumentos de valoración nutritiva para predecir una mala evolución clínica en hospitalizados - M. G. Beghetto; V. C. Luft; E. D. Mello; C. A. Polanczyk (Nutrición Hospitalaria, 2009)
Background and aims: The ability of nutritional status assessment methods to predict clinical outcomes in hospitalized patients has not been completely evaluated. This study compared the accuracy of traditionally used nutritional tools and parameters in predicting death, infection, and length of hospital stay (LOS) in hospitalized adults. Research Methods & Procedures: Patients admitted at clinical and surgical wards were evaluated by body mass index, percentage of weight loss, Subjective Global Assessment, albumin, lymphocyte count, and followed until discharge. Clinical outcomes considered were inhospital death, infection, and LOS. Overall accuracy of each method to predict these outcomes was assessed from ROC curves and C-statistic. Results: Among 434 patients evaluated, 51% had a prolonged LOS, 23% developed infection, and 7.8% died during hospitalization. In univariate analysis, serum albumin was the strongest predictive parameter for death (Cstatistic: 0.77; CI95%: 0.69-0.86) and hospital infection (C-statistic: 0.67; CI95%: 0.61-0.74). For longer stay, lymphocyte count (C-statistic: 0.60; CI95%: 0.55-0.65) emerged as the most predictive variable. After adjustment for non-surgical hospitalization and cancer diagnosis, weight loss > 5% (OR: 1.58; CI95%: 1.06-3.35), and serum albumin < 3.5 g/dL (OR: 2.40; CI95%: 1.46-3.94) were associated to LOS. Albumin was the only independent variable related to infection (OR: 5.01; CI95%: 3.06-8.18) and, for hospital death, albumin (OR: 7.20; CI95%: 3.39-15.32) adjusted for age (OR: 1.03; CI95%: 1.01-1.06). Conclusions: Nutritional assessment methods evaluated were weakly predictors of hospital outcomes. Except for low serum albumin, isolated use of these methods adds little information in identifying the effect of nutritional status on clinically relevant outcomes. Conocimientos previos y objetivos: No se ha evaluado de forma completa la fiabilidad de los métodos de evaluación del estado nutritivo para predecir la evolución clínica de los pacientes hospitalizados. Este estudio comparó la precisión de instrumentos tradicionales y de parámetros en la predicción de muerte, infección y duración de hospitalización (DH) en adultos hospitalizados. Métodos de investigación y procedimientos: Se evaluó a pacientes ingresados en guardias médicas y quirúrgicas, empleando el índice de masa corporal, el porcentaje de pérdida de peso, la Valoración Subjetiva Global, la albúmina y el recuento linfocitario, y se les siguió hasta ser dados de alta. Resultados: Entre los 434 pacientes evaluados, el 51% tuvo una DH prolongada, el 23% desarrolló infección y el 7,8% murió durante la hospitalización. En el análisis de univarianza, el factor predictivo de muerte más potente fue la albúmina sérica (C-estadística: 0,67; IC95%: 0,61- 0,74) y también de infección hospitalaria (C-estadística: 0,67; IC95%: 0,61-0,74). En el caso de una mayor DH, la variable predictiva más fiable fue el recuento linfocitario (C-estadística: 0,60; IC95%: 0,55-0,65). Tras realizar el ajuste de hospitalización no quirúrgica y diagnóstico de cáncer, la pérdida de peso > 5% (OR: 1,58; IC95%: 1,06- 3,35) y la albúmina sérica < 3,5 g/dl (OR: 2,40; IC95%:1,46- 3,94) se asociaban a la DH. La albúmina fue la única variable independiente relacionada con la infección (OR: 5,01; IC95%:3,06-8,18) y, en el caso de muerte hospitalaria, la albúmina (OR: 7,20; IC95%:3,39-15,32) ajustada en función de la edad (OR: 1,03; IC95%:1,01-1,06). Conclusiones: Los métodos de valoración nutritiva evaluados fueron predictores débiles de la evolución clínica hospitalaria. Exceptuando la albúmina sérica baja, la determinación aislada de estos parámetros añade poca información para identificar el efecto del estado nutricional sobre la evolución clínica.